Delving Deeper Into the Construct of Preservice Teacher Beliefs About Reading Instruction for Students With Disabilities. (August 2015) - Leko, Melinda M.; Kulkarni, Saili; Lin, Meng-Chuan; Smith, Shane A.
The purpose of this study was to complete an in-depth examination of the construct of teacher beliefs by investigating preservice teachers' beliefs about reading instruction for students with disabilities. Interview and artifact data were collected for 11 preservice teachers during a 10-month period. Dimensions of beliefs investigated were expressed beliefs and beliefs-in-use, the stability of beliefs, and sources of beliefs. Results indicate that preservice teachers' beliefs systems are complex, made up of enduring, deeply rooted expressed beliefs as well as beliefs-in-use that are highly dependent on discipline-specific working knowledge. These beliefs are not the same in how they are formed or sustained; thus, an implication of this study's findings is that researchers and teacher educators be more specific and explicit when describing studies of preservice teacher beliefs. Additional implications for future research and practice regarding the relationship between teacher beliefs and teacher education are provided.